2021
DOI: 10.3390/nu13124371
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously Low Protein Intake in Elderly CKD Patients: Myth or Reality? Analysis of Baseline Protein Intake in a Large Cohort of Patients with Advanced CKD

Abstract: The recent guidelines on nutritional management of chronic kidney disease (CKD) advise a reduction in protein intake as early as CKD stage 3, regardless of age, to slow kidney function impairment. However, since elderly patients are usually considered as having a spontaneously reduced protein intake, nutritional interventions to reduce protein intake are often considered futile. This study aimed to assess the baseline protein intake of elderly CKD patients referred for nephrology care, and explore the need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Results of this multicohort study are in line with those of observational studies [10][11][12] that have found neutral or inverse associations between protein intake and mortality among older persons with CKD stages 3 to 5 not receiving dialysis. First, in 3892 middle aged and older Korean adults, higher total protein intake showed a null association with 11-year all-cause mortality.…”
Section: Discussion Interpretationsupporting
confidence: 89%
See 2 more Smart Citations
“…Results of this multicohort study are in line with those of observational studies [10][11][12] that have found neutral or inverse associations between protein intake and mortality among older persons with CKD stages 3 to 5 not receiving dialysis. First, in 3892 middle aged and older Korean adults, higher total protein intake showed a null association with 11-year all-cause mortality.…”
Section: Discussion Interpretationsupporting
confidence: 89%
“…10 Second, among 356 French patients with CKD over 60 years, higher total protein intake was not associated with increased mortality after 3 years. 12 Third, in 259 Japanese adults with CKD and older than 65 years, higher total protein intake was associated with lower risk of all-cause death over 4 years, although participants had been advised to limit protein intake depending on their CKD stage. 11 The latest Cochrane systematic reviews 13,14 of randomized clinical trials found that among adults of all ages without diabetes and with CKD, protein intake of either 0.30 to 0.40 or 0.50 to 0.60 g/kg/d probably does not influence the risk of death when compared with 0.80 g/kg/d or greater, while in adults with diabetic kidney disease, protein intake of 0.60 to 0.80 g/kg/d may make little difference in the risk of mortality when compared with 1.00 g/kg/d or greater.…”
Section: Discussion Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in France referred that even in elderly CKD patients the protein content is higher than recommended, they are mostly spontaneous in diet and indicates there is a need for nutritional care for this population [54].…”
Section: Protein Restriction In Diabetic Patients With Ckd (Not On Di...mentioning
confidence: 99%
“…Based on some large population studies, it is commonly held that, since protein intake decreases with age and is overall lower in advanced CKD, reducing protein intake in the elderly CKD population is a sterile and useless exercise [ 121 , 122 ]. While this may be true in those cases that are already stabilized with a spontaneous reduction in protein intake, data from our group in Central France suggest that protein intake exceeds 1.2 g/kg/day in about 20% of CKD patients (Stages 3–5 not on dialysis) aged 90 years or above, and is over the 0.6 target in about 60% of CKD patients aged over 80 years [ 123 ].…”
Section: Elderly Patients: the Importance Of Restoring “Traditional” ...mentioning
confidence: 99%